Ahmad Warson Wa Manhajuhu Fi Ta’lifi Qamus Al-Munawwir - Zughrofiyatun Najah; Ahmad Nur Mizan (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
Dictionary defines a book consisting of set of vocabularies that are taken from the original or adoption language. The main purpose of the study is to explore the method used by Ahmad Warson  Munawwir in arranging Arab–Indonesian Munawwir dictionary, in term of similarities and differences between both dictionaries. This study is library research with qualitative analysis; therefore, the researchers use documentary method to collect the data, in particular, the matters explain the arrangement method of this dictionary. In analyzing the data, the researcher uses Bibliography Method to find out the acts and histories of some figures and the dictionary. Descriptive method is used to describe and analyze the data about the arrangement method of this dictionary. From analyzing the data, the researcher reveals some conclusion, such as 1) the chapters of this dictionary are arranged according to Hijaiyyah Letters sequences. 2) this dictionary is divided into two parts; the first part consists of vocabularies and the second part consists of pictorial vocabularies and cases associated with important events in the world, 3) this dictionary adds sentences as the explanation of the words, 4) Munawwir Dictionary is multilanguage translation dictionary, 5) Munawwir Dictionary explains the words meaning using two languages, they are Arabic to Arabic and Arabic to Indonesian. 6) Ahmad Warson  Munawwir doesn’t clarify the pictorial vocabularies in the dictionary by giving the main title yet.